Effect of prenatal multiple micronutrient supplementation on birth weight in Ethiopia: protocol for a pragmatic cluster-randomised trial - Joanna Schellenberg; Charles Opondo; Tanya Marchant; Lars Åke Persson; Masresha Tessema; Atkure Defar; Alemneh Kabeta Daba; Girum Taye; Senait Alemayehu; Elias Asfaw; Anene Tesfa; Bedasa Tessema; et al. (BMJ Open)
Introduction This programme effectiveness study responds to the need for evidence of the effect on birth weight of switching from iron-folic acid supplementation to multiple micronutrient supplementation as part of routine antenatal care in Ethiopia. A 2019 meta-analysis reported a mean increase of 35 g in birth weight among newborns of women who took multiple micronutrient supplements in pregnancy compared with those who took iron-folic acid. Responding to that evidence, the government of Ethiopia decided to implement a 21 district pilot of the use of multiple micronutrient supplementation in routine antenatal care and requested an evaluation of implementation outcomes, including on birth weight.Methods and analysis A pragmatic, facility-based, randomised trial is being conducted in 42 districts over five regions of Ethiopia between January 2023 and December 2024. Districts have been randomised to one of the two arms, either to retain iron-folic acid supplementation as part of routine antenatal care or switch to multiple micronutrient supplementation. During the study period, the birth weights of all eligible babies born in enrolled health facilities in these 42 districts are continuously recorded alongside data on maternal receipt and use of either multiple micronutrient or iron-folic acid supplementation. We hypothesise that newborns of women resident in the 21 multiple micronutrient supplementation districts will have higher mean birth weight than newborns of women resident in the 21 iron-folic acid supplementation districts. Facility surveys involving pregnant women and healthcare workers at baseline, midline and endline contribute to a process evaluation and cost and cost-effectiveness evaluation.Ethics and dissemination The study received ethical approval from the review boards at the Ethiopian Public Health Institute (EPHI-IRB-455-2022) and the London School of Hygiene & Tropical Medicine (LSHTM ref 28021). Results from this pragmatic trial will be used by the government of Ethiopia in assessing success of the multiple-micronutrient supplements pilot and for decision making about subsequent scale-up. Dissemination of findings will also inform global decision making, particularly in settings where a transition from iron-folic acid to multiple micronutrient supplementation is being contemplated at scale.Trial registration number NCT05708183.